Fanfiction e práticas de letramentos na internet - Alves, Elizabeth Conceição de Almeida (2014)
We live currently in a virtualized world where media and digital media have been part of the experience of young people and adolescents. These users have used the internet to play games, participate in chat chats and to create stories. Considering this scenario, this paper aims to investigate how adolescents are writing in the digital environment by participating in on-line communities, such as Fanfiction. Researches are based in theoretical studies of literacy (STREET, 1984, COPE; KALANTZIS, 2000, LANKSHEAR; KNOBEL, 2005, MENEZES DE SOUSA; MONTE MÓR, 2006, SOARES, 2006, TAKAKI, 2012), new literacies (LANKSHEAR; KNOBEL, 2007, LOPES, 2010), and multiliteracies (ROJO, 2012, 2013). On the concept of participatory culture(CHARTIER, 2009; JENKINS, 2009; SANTAELLA, 2007). Regarding the fanfiction (JENKINS, 2009; VARGAS, 2005). This research questions that drove this study: 1) What meanings do teens give in relation to the writing in digital context? 2) How unfolds in the process of writing fanfiction? The interpretive approach was adopted research methodology with analysis of dialogues generated through interviews with the participants (BORTONI-RICARDO, 2009, FLICK, 2009). From the recurring themes and categories analyzed, the results could signal that the process of writing in the digital environment is composed of, collaborative dynamically permeated by affective and mediated screen values.